Granulite accretion to Rio de la Plata Craton, based on zircon U-Pb-Hf isotopes: tectonic implications for Columbia Supercontinent reconstruction - GIRELLI, Tiago Jonatan (2018)
The paleogeographic reconstruction of the Rio de la Plata involved eitherallocthonous or autochthonous process reflecting directly the Paleoproterozoic connection of the craton to Columbia Supercontinent. Santa Maria Chico Granulite Complex is a significant fragment of Rio de la Plata intensely affected bythe Brasiliano Orogeny. ZirconU-Pb-Hf isotopes by LA-ICP-MS, mineral and whole-rock chemistry and a pseudo-section are presentlyinterpreted. U-Pb-Hf isotopes characterize two main accretionary and metamorphic events: oceanic juvenilecrustal accretion (i) 2430–2290 Ma (εHf (t) = −3.17 to +7.00), with arc related metamorphism (830–870 °C,6.7–7.2 kbar) at ~2.3 Ga;and continental arc accretion (ii)2240–2120 Ma(εHf (t) = −4 to +2.4), with continen- talcollisionmetamorphism(770–790 °C,8.7–9.1 kbar)at2.1–2.0 Ga.Alkalinegraniticdikesrelatedtocrustalex- tension at 1.8 Ga cut the granulitic rocks after the stabilization of this crustal segment. The present data point to formation of Paleoproterozoic granulitic rocks of the Santa Maria Chico Granulite Complex and adjacent Nico Pérez and Rivera terranes in multi-stage volcanic arcs to continental collision environment over 370 Ma (2430 to 2060 Ma). These terranes were amalgamated in the Paleoproterozoic to the core of the Rio de la Plata Cratonas part of Columbia Supercontinent and intensely reworked during the amalgamation of Western Gondwana inthe Neoproterozoic.